How Can Project-Based Learning Enhance 21st Century Skills in Islamic Elementary Schools? Exploring Its Impact on Critical Thinking, Creativity, Communication, and Collaboration - 'Azizah, Wida Nurul; Dewanti, Sintha Sih; Prasetyo, Sigit; Fatonah, Siti; Zerenay, Ceyda (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study investigates the effectiveness of Project-Based Learning (PjBL) in enhancing 21st-century skills, specifically critical thinking, creativity, communication, and collaboration (4Cs), in elementary school science education. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, synthesizing findings from 40 empirical studies published between 2020 and 2025. The results demonstrate that PjBL significantly improves students’ scientific literacy, engagement, and problem-solving skills by providing real-world, hands-on learning experiences. PjBL encourages collaborative learning environments where students actively engage in projects, thereby enhancing their 4C competencies. However, the study also identifies challenges, such as teacher readiness, limited resources, and curriculum constraints, which hinder the full implementation of PjBL in elementary schools. Despite these obstacles, the research underscores the importance of teacher professional development and resource availability in optimizing the effectiveness of PjBL. The findings of this study contribute to the growing body of research on innovative pedagogies, offering practical insights for educators and policymakers seeking to foster essential 21st-century skills in young learners. This study provides valuable evidence supporting the integration of PjBL into elementary science curricula, highlighting its role in preparing students for future challenges.